ESTIMULACION TEMPRANA Y SU INCIDENCIA EN NIÑOS CON DEFICIT DE ATENCION E HIPERACTIVIDAD DEL INICIAL I - ALVAREZ ANCHUNDIA BELEN XIOMARA (2024)
The present research is titled early stimulation and its incidence in children with attention deficit and hyperactivity of Initial I, considering that TDAH, or attention deficit and hyperactivity disorder, is a neurological condition that affects around 5% of children. children, which gives rise to the investigation because in the Emigdio Esparza Educational Unit there is evidence of the presence of children who present signs of Attention Deficit and Hyperactivity Disorder (TDAH), including impulsivity, difficulty concentrating or remaining still and lack of attention . , above all, they do not receive enough early stimulation, which should include social and emotional development techniques, structured and focused activities that help them concentrate and exercise self-control, and personalized attention. Therefore, the objective of the research is to determine the incidence of early stimulation in children with attention deficit and hyperactivity of Initial I, which to meet the objective of the research, a non-experimental cross-sectional methodological design is executed, whose method It is the inductive method with a descriptive scope with a mixed approach, whose type of research is field research in a combination of techniques such as observation, interview and survey and instruments such as the observation sheet and questionnaires that allow collecting the necessary information to give validity to the research, considering that if these children are stimulated early they can have a positive impact such as improving their concentration, controlling their impulses and developing new social skills, in conclusion early stimulation is an effective tool to help children in Education Initial I.